Prolematika Pengelolaan Pendidikan Islam Non-Formal Pada Komunitas Muslim - Rivai Bolotio; Hadirman Hadirman; Musafar Musafar (IAIN Manado, 2021)
Prolematics of Non-Formal Islamic Education Management in Muslim Communities. This article aims to describe the prolematics of managing non-formal Islamic education in the Muslim community, specifically TPQ Nurul Taqwa Sea in Sea Village, Pineleng District, Minahasa Regency. Management problems in non-formal education, specifically TPQ Nurul Taqwa Sea are related to the non-optimally implementation of institutional management based on management functions (planning, organizing, monitoring and evaluating). In addition, it also illustrates the driving and inhibiting factors in the management of TPQ Nurul Taqwa Sea relating to (1) curriculum and teaching, (2) teaching staff, (3) students, (4) facilities and infrastructure, (5) finance and financing, (6) TPQ's relationship with the community